Knowledge and Attitude Towards Assessment and Testing Among School and Other Practising Counsellors in Nigeria - Osumah, Obaze Agbonluae; Ehigbor, B. O.; Osemeikhian, Edowaye (Department of Guidance and Counseling, FIP, Undiksha, 2024)
This study addressed the problem of limited knowledge and varying attitudes towards assessment and testing among school and practicing counsellors in Nigeria. The research aimed to explore the relationships between knowledge and attitudes towards these practices. Using four research questions and hypotheses, the study targeted all counsellors in Nigeria, with a purposive random sample of 350 participants drawn from attendees at the annual APROCON and CASSON conferences. Data were collected through the